Intraerythrocytic stages of Plasmodium falciparum biosynthesize menaquinone - Tonhosolo, Renata (FEBS Lett, 2010)
Herein, we show that intraerythrocytic stages of Plasmodium falciparum have an active pathway for biosynthesis of menaquinone. Kinetic assays confirmed that plasmodial menaquinone acts at least in the electron transport. Similarly to Escherichia coli, we observed increased levels of menaquinone in parasites kept under anaerobic conditions. Additionally, the mycobacterial inhibitor of menaquinone synthesis Ro 48-8071 also suppressed menaquinone biosynthesis and growth of parasites, although off-targets may play a role in this growth-inhibitory effect. Due to its absence in humans, the menaquinone biosynthesis can be considered an important drug target for malaria.